Reflections on Self-Reflection: Contemplating Flawed Self-Judgments in the Clinic, Classroom, and Office Cubicle. (March 2018) - Dunning, David; Heath, Chip; Suls, Jerry M.
We reflect back on our 2004 monograph reviewing the implications of faulty self-judgment for health, education, and the workplace. The review proved popular, no doubt because the importance of accurate self-assessment is best reflected in just how broad the literature is that touches on this topic. We discuss opportunities and challenges to be found in the future study of self-judgment accuracy and error, and suggest that designing interventions aimed at improving self-judgments may prove to be a worthwhile but complex and nuanced task.